Correlations Between Fish Assemblage Structure and Environmental Variables of Taruwa Pond in Nawalparasi District, Province No. 4, Nepal - LIMBU, JASH HANG; CHAUDHARY, KESHI (Borneo Journal of Resource Science and Technology, 2021)
The correlations between fisheries diversity and environmental variables of Nepal’s Pond are poorly understood. This study aims to investigate temporal variation of fish assemblage at Taruwa Pond in Nawalparasi district, Province no. 4, Nepal from October 2018 to April 2019. For the fish agglomeration, cast net of 4 kg in weight and 3.80 m in length and 22.5 m breadth with 12 mm mesh size was used. In total, 579 individuals representing 16 fish species, 10 families, and 12 genera were recorded. According to similarity percentage analysis, the most contributory species were Puntius ticto (27.92%) followed by Danio devario (12.06%), Puntius terio (9.76%), Badis badis (7.31%), Lepidocephalichthys guntea (5.57%) and Puntius sophore (5.57%). Analysis of similarity suggested that fish community structure was significantly different in temporal variation (R = 0.321, p<0.01). Based on the cluster analysis, fish assemblages were isolated into two distinct groups at Bray-curtis similarity. The Canonical Correspondence Analysis distinctly indicated that the water parameters of dissolved oxygen, carbon-dioxide, depth, and water temperature play an important role in influencing the fish assemblage structure of Taruwa Pond.